Nutrition intake in the post-ICU hospitalization period. Issue 2 (March 2020) - Ridley, Emma J.; Chapple, Lee-anne S.; Chapman, Marianne J.
Abstract : Purpose of review: The care of critically ill patients has evolved over recent years, resulting in significant reductions in mortality in developed countries; sometimes with prolonged issues with recovery. Nutrition research has focused on the early, acute period of critical illness, until more recently, where the post-ICU hospitalization period in critical care survivors has become a focus for nutrition rehabilitation. In this period, nutrition rehabilitation may be a vital component of recovery. Recent findings: Overall, oral nutrition is the most common mode of nutrition provision in the post-ICU period. Compared with oral intake alone, calorie and protein requirements can be better met with the addition of oral supplements and/or enteral nutrition to oral intake. However, calorie and protein intake remains below predicted targets in the post-ICU hospitalization period. Achieving nutrition targets are complex and multifactorial, but can primarily be grouped into three main areas: patient factors; clinician factors; and system factors. Summary: A nutrition intervention in the post-ICU hospitalization period may provide an opportunity to improve survival and functional recovery. However, there are multiple barriers to the delivery of calculated nutrition requirements in this period, a limited understanding of how this can be improved and how this translates into clinical benefit.